2016
DOI: 10.1002/bmc.3785
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative determination of buprenorphine, naloxone and their metabolites in rat plasma using hydrophilic interaction liquid chromatography coupled with tandem mass spectrometry

Abstract: A rapid and sensitive LC-MS/MS method was developed and validated for the simultaneous determination of buprenorphine and its three metabolites (buprenorphine glucuronide, norbuprenorphine and norbuprenorphine glucuronide) as well as naloxone and its metabolite naloxone glucuronide in the rat plasma. A hydrophilic interaction chromatography column and a mobile phase containing acetonitrile and ammonium formate buffer (pH 3.5) were used for the chromatographic separation. Mass spectrometric detection was achiev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Compared to other works, this result is more than satisfactory. Authors who used simple protein precipitation [23,36] reported lower values (80-91%), which proves the very efficient drug extraction in the current protocol.…”
Section: Extraction Proceduresmentioning
confidence: 77%
“…Compared to other works, this result is more than satisfactory. Authors who used simple protein precipitation [23,36] reported lower values (80-91%), which proves the very efficient drug extraction in the current protocol.…”
Section: Extraction Proceduresmentioning
confidence: 77%
“…A bioanalytical method was developed and validated for the determination of BUP, BUPG, NBUP, NBUPG, NX and NXG in K 2 EDTA rat plasma . Analysis was performed by UPLC coupled to a mass spectrometer (as described below) with calibration ranges of 1.0–1000 ng/ml for BUP, BUPG, NXG and NBUPG, and 5.0–1000ng/ml for NX and NBUP, respectively; samples above this range were diluted with blank rat plasma.…”
Section: Methodsmentioning
confidence: 99%
“…The mass transitions for different analytes are as follows: BUP 468.3 > 396.0, BUP‐d4 472.4 > 400.3, BUPG 644.3 > 468.5, NBUP 414.2 > 101.4, NBUP‐d3 417.4 > 187.2, NBUPG 590.3 > 414.4, NBUPG‐d3 593.2 > 417.3, NX 328.3 > 310.2, NX‐d5 333.0 > 315.4, NXG 504.0 > 310.1 and NXG‐d5 509.3 > 212.2. NBUPG‐d3 was synthesized from NBUP‐d3 enzymatically using LS180 cells known to possess high glucuronidation activity …”
Section: Methodsmentioning
confidence: 99%
“…Reference Cohier et al 55 Ransohoff et al 59 Joshi et al 52 Swortwood et al 51 McMillin et al 49 Al-Asmari and Anderson 40 triple quadrupole mass analyser operated with positive electrospray ionization and MRM. However, a variety of different analytical approaches was taken in terms of sample preparation and chromatographic separation methods.…”
Section: T a B L E 4 Comparison Of Previous Lc-ms/ms Quantification M...mentioning
confidence: 99%
“…Liquid chromatography–tandem mass spectrometry (LC‐MS/MS)‐based methods, with or without hydrolysis of conjugates, are commonly used to analyse one or more of the analytes BUP, NBUP, NAL, BUP‐G, NBUP‐G, and NAL‐G 35–55 . However, to our knowledge, to date, there is no published LC‐MS/MS method for the simultaneous quantification of all six analytes, including NAL‐G, in human urine.…”
Section: Introductionmentioning
confidence: 99%